Peripheral Ulcerative Keratitis A Comprehensive Guide - Tandon, Radhika; Galor, Anat.; Sangwan, Virender Singh; Ray, Manotosh; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
A handy manual for cornea specialists, this book provides detailed practical information about a complex, sight-threatening disease that can be challenging to diagnose and manage. This text features chapters dedicated to outlining all facets of diagnosis and management while covering both medical and surgical treatment options. Peripheral Ulcerative Keratitis, supplemented with useful references and appendices to provide simple step by step algorithms, is written by internationally renowned authors who are experts in the field. Including practical tips and guidelines for diagnosis and therapy of these disorders, Peripheral Ulcerative Keratitis is designed to serve as a guide for comprehensive ophthalmologists and should find itself on the bookshelves of ophthalmology clinics, corneal practices and training programs across the country. .
Section 1: Basics -- 1. Peripheral Ulcerative Keratitis: Anatomical Considerations -- 2. Peripheral Ulcerative Keratitis: Etiopathogenesis -- 3. Peripheral Ulcerative Keratitis: Clinical Evaluation -- 4. Peripheral Ulcerative Keratitis: Investigative Modalities -- 5. Peripheral Ulcerative Keratitis: General Principles of Medical Therapy -- 6. Peripheral Ulcerative Keratitis: General Principles of Surgery -- Section 2: Clinical Overview -- 7. Peripheral Ulcerative Keratitis: Clinical Syndromes, Classifications, and Differential Diagnosis -- 8. Peripheral Ulcerative Keratitis: Infectious Causes -- 9. Peripheral Ulcerative Keratitis: Non-Infectious Causes -- Section 3: Guide to Treatment -- 10. Peripheral Ulcerative Keratitis: Medical Therapy Algorithms -- 11. Peripheral Ulcerative Keratitis: C-shaped Lamellar Corneal Patch Grafts--(3z(BMatch and Patch(3y (BTechnique -- 12. Peripheral Ulcerative Keratitis: Practical Guide to Immunomodulatory Agents.s
Keywords: Medicine; Ophthalmology; Medicine & Public Health; Ophthalmology